Brill's companion to Nonnus of Panopolis - Accorinti, Domenico. (Brill's Companions to Classical Studies., 2016)
The Egyptian Nonnus of Panopolis (5th century AD), author of both the 'pagan' Dionysiaca , the longest known poem from Antiquity (21,286 lines in 48 books, the same number of books as the Iliad and Odyssey combined), and a 'Christian' hexameter Paraphrase of St John's Gospel (3,660 lines in 21 books), is no doubt the most representative poet of Greek Late Antiquity. Brill's Companion to Nonnus of Panopolis provides a collection of 32 essays by a large international group of scholars, experts in the field of archaic, Hellenistic, Imperial, and Christian poetry, as well as scholars of late antique Egypt, Greek mythology and religion, who explore the various aspects of Nonnus' baroque poetry and its historical, religious and cultural background.